Analisis Pengaruh Fraud Pentagon Terhadap Fraudulent Financial Reporting Menggunakan Beneish Model - Dwi Reski Marham Novianti; Abdul Hamid Habbe; Nirwana Nirwana (Bongaya Journal of Research in Accounting (BJRA), 2022)
This study discusses the analysis of the influence of Pentagon Fraud on Fraudulent Financial Reporting using the Beneish Model. Pentagon fraud is an independent variable in this study. Proxies that can be used for this research include pressure which is proxied by financial targets and financial stability. Opportunity (opportunity) which is proxied by ineffective monitoring and quality of external auditors. Rationalization (Rationalization) which is proxied by change in auditor and auditor's opinion. Capability which is proxied by the change of the company's directors. Arrogance is proxied by the frequent number of CEO's picture and CEO politician. The dependent variable uses Fraudulent Financial Reporting which is measured using the Beneish Model. This model uses 8 (eight) calculation ratios, namely, Days Sales in Receivable Index (DSRI), Gross Margin Index (GMI), Asset Quality Index (AQI), Sales Growth Index (SGI), Depreciation Index (DEPI), Sales and General Administration Expenses Index (SGAI), Leverage Index (LVGI), and Total Accrual (TATA). The object of research is a company that is included in the LQ-45 index for the 2019-2020 period listed on the Indonesia Stock Exchange (IDX), the sample taken for the study is 33 companies based on the Purposive Sampling method. The results of this study are (1) Financial stability (ACHANGE) has a significant effect on Fraudulent Financial Reporting. (2) Financial target (ROA), Ineffective Monitoring (BDOUT), Quality of external auditor (KAE), Change in auditor (AUDCHANGE), Opinion auditor (AO), Change in Board of Director (DCHANGE), Frequent number of CEO's picture (CEOPIC) and Politicians (OSHIP) have no significant effect on Fraudulent Financial Reporting.